2009
DOI: 10.1177/1090198109338919
|View full text |Cite
|
Sign up to set email alerts
|

Intention, Subjective Norms, and Cancer Screening in the Context of Relational Culture

Abstract: Research targeting disparities in breast cancer detection has mainly utilized theories that do not account for social context and culture. Most mammography promotion studies have used a conceptual framework centered in the cognitive constructs of intention (commonly regarded as the most important determinant of screening behavior), self-efficacy, perceived benefit, perceived susceptibility, and/or subjective norms. The meaning and applicability of these constructs in diverse communities are unknown. The purpos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 39 publications
4
77
0
Order By: Relevance
“…These findings are consistent with previous studies that have found that providing information to family members, particularly children, is one of the most important predictors of interest in and/or intention to obtain GT for a variety of hereditary cancers (Kinney et al 2000(Kinney et al , 2001Lerman et al 1995;Ulrich et al 1998). Given the importance placed on the family in Hispanic culture, health care decisions have been found to be made more collectively, which supports these findings (Flores 2000;Granda-Cameron 1999;Pasick et al 2009). …”
Section: Knowledge About Hereditary Cancer By Locationsupporting
confidence: 82%
“…These findings are consistent with previous studies that have found that providing information to family members, particularly children, is one of the most important predictors of interest in and/or intention to obtain GT for a variety of hereditary cancers (Kinney et al 2000(Kinney et al , 2001Lerman et al 1995;Ulrich et al 1998). Given the importance placed on the family in Hispanic culture, health care decisions have been found to be made more collectively, which supports these findings (Flores 2000;Granda-Cameron 1999;Pasick et al 2009). …”
Section: Knowledge About Hereditary Cancer By Locationsupporting
confidence: 82%
“…When a person declares an intention to do something, the likelihood of that behaviour taking place is high. Although one previous study maintains that there are differences in the meaning of a declared intention among different cultures and that having an intention does not necessarily entail the action being performed (Pasick et al, 2009), others believe that the intention is still chosen as an outcome when an actual screening cannot be measured (Ham, 2005;Levy-Storms and Wallace, 2003).…”
Section: Introductionmentioning
confidence: 96%
“…Among the findings, when analyzed within the domain of relational culture (the processes of interdependence and interconnectedness among individuals within families and groups), the construct of intention was found to have many meanings that conflict with that defined in the TPB (76). As part of the same study, Washington et al (106) conducted video-taped observations of Filipina and Latina mother-daughter dyads discussing breast cancer screening.…”
Section: Theory Of Planned Behaviormentioning
confidence: 99%